Covalent immobilization of microbial naringinase using novel thermally stable biopolymer for hydrolysis of naringin - Awad, G.; Abd El Aty, A.; Shehata, A.; Hassan, M.; Elnashar, Magdy (Springer, 2016)
Naringinase induced from the fermented broth of marine-derived fungus Aspergillus niger was immobilized into grafted gel beads, to obtain biocatalytically active beads. The support for enzyme immobilization was characterized by ART-FTIR and TGA techniques. TGA revealed a significant improvement in the grafted gel’s thermal stability from 200 to 300 °C. Optimization of the enzyme loading capacity increased gradually by 28-fold from 32 U/g gel to 899 U/g gel beads, retaining 99 % of the enzyme immobilization efficiency and 88 % of the immobilization yield. The immobilization process highly improved the enzyme’s thermal stability from 50 to 70 °C, which is favored in food industries, and reusability test retained 100 % of the immobilized enzyme activity after 20 cycles. These results are very useful on the marketing and industrial levels.